Onset and maximum values of electromyographic amplitude during prone hip extension after neurodynamic technique in patients with lumbosciatic pain: A pilot study. Issue 2 (April 2016) - Horment-Lara, Giselle; Cruz-Montecinos, Carlos; Núñez-Cortés, Rodrigo; Letelier-Horta, Pablo; Henriquez-Fuentes, Luis
Summary: Objective: The mechanisms underlying the effects of neurodynamic techniques are still unknown. Therefore, the aim of this study was to provide a starting point for future research on explaining why neurodynamic techniques affect muscular activities in patients with sciatic pain. Methods: A double-blind trial was conducted in 12 patients with lumbosciatica. Surface electromyography activity was assessed for different muscles during prone hip extension. Pre- and post-intervention values for muscle activity onset and maximal amplitude signals were determined. Results: There was a significant reduction in the surface electromyography activity of maximal amplitude in the erector spinae and contralateral erector spinae ( p < 0.05). Additionally, gluteus maximus ( p < 0.05) activity onset was delayed post-intervention. Conclusions: Self-neurodynamic sliding techniques modify muscular activity and onset during prone hip extension, possibly reducing unnecessary adaptations for protecting injured components. Future work will analyze the effects of self-neurodynamic sliding techniques during other physical tasks.